The genus "Roccella" in the Iberian Peninsula and Balearic Islands - Carballal, Regina (Botanica Complutensis, 2013)
The morphological, anatomical, chemical and geographical data of 6 species of genus Roccella is reported from the Iberian Peninsula andBalearic Islands. An identification key based in macroscopic characters and chemical reactions is presented. Roccella elisabethae is recorded forthe first time from continental Europe.